2017
DOI: 10.2174/1874471009666161117120358
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-labeled White Blood Cell Scan as a Guide to Open Biopsy in the Management of Hip and Knee Prosthesis Infection: Preliminary Results

Abstract: The obtained results indicate that a multidisciplinary approach to infection of orthopedic prostheses, characterized by the combined use of open biopsy, WBC, and microbiological examination, produced positive outcome in 9 out of 14 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Advanced detection methods such as X-ray computed tomography (99mTc-WBC SPECT/CT) and white blood cell scanning, which can analyze the prognosis of diabetic foot infection, are not available in China. 29,30 Therefore, the STAGE principles cannot be used to objectively determine the depth of the target anatomical layer for incision. The assessment of the incision depth still depends on clinical experience.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced detection methods such as X-ray computed tomography (99mTc-WBC SPECT/CT) and white blood cell scanning, which can analyze the prognosis of diabetic foot infection, are not available in China. 29,30 Therefore, the STAGE principles cannot be used to objectively determine the depth of the target anatomical layer for incision. The assessment of the incision depth still depends on clinical experience.…”
Section: Discussionmentioning
confidence: 99%
“…In its starting era, it used different radioisotopes clinically to catch the glimpse of DSI; however, after the discovery of 99m Tc radionuclide having patient friendly characteristics (short half‐life 6 hr, isomeric transition (gamma) decay process, and adequate gamma photon energy 140 Kev), variety of biological and synthetic molecules were labeled with 99m Tc for infection and tumor imaging. Initially, the 99m Tc‐WBC and 67 Ga ‐citrate radiopharmaceutical were clinically used for infection imaging with low to high sensitivity (Liberatore et al, 2017; Palestro et al, 2013). However, due to multiple demerits associated with 99m Tc‐WBC and 67 Ga ‐citrate, new infection imaging radiotracers were studied.…”
Section: Mtc‐labeled Antibiotics and Their Efficacymentioning
confidence: 99%
“…Similar to previous studies, SPECT/CT allowed more accurate localization of abnormal uptake on bone and white cell scintigraphy. Recently, preliminary results of a study by Liberatore et al [29] showed potential of white blood cell scan as a guide to open biopsy in the management of hip and knee prosthesis infection.…”
Section: Data Extractionmentioning
confidence: 99%